Levels of literacy among juvenile offenders: The incidence of specific reading difficulties - Snowling, M; Adams, J; Bowyer-Crane, C; Tobin, V (2000)
Introduction: Academic achievement is low among offenders. Yet there is little evidence that prisoners are less literate than the general population. Do they have more dyslexia? This paper considers three definitions of dyslexia to see whether they relate to young offenders' literacy difficulties. Method: The reading and spelling skills of 91 15- to 17-year-old male juvenile offenders who were incarcerated are reported, together with assessments of their vocabulary and non-verbal (spatial) skills. Estimates of the prevalence of reading disability are considered in relation to different definitions of dyslexia. Results: The regression of literacy skills on non-verbal ability yielded an estimated prevalence of 57% while a more conservative estimate of 43% followed from the regression of literacy skill on verbal ability, and 38% of the sample had specific phonological deficits. Many of the offenders had experienced social and family adversity and reported poor school attendance. Discussion: It is proposed that as a group, juvenile offenders are best described as having general verbal deficits encompassing problems of language and literacy.